Scientific and Computational Challenges in Coupled Plasma Edge/Plasma‐Material Interactions for Fusion Tokamaks. Issue 4 (June 2014) - Brooks, J. N.; Hassanein, A.; Koniges, A.; Krstic, P. S.; Rognlien, T. D.; Sizyuk, T.; Sizyuk, V.; Stotler, D. P.
Abstract Plasma/material interactions is a critical scientific issue for fusion power, with major potential limitations on plasma core and edge operating parameters. Gaining understanding and predictive capability in this area will require simultaneously addressing complex and diverse physics occurring over a wide range of lengths (angstroms to meters) and times (femtoseconds to days). This requires further development and validation of detailed physics models and computational strategies at each of these scales. The overriding numerical need is for petascale real‐time coupling between 3‐D material response/evolution/trapping codes, plasma edge/SOL codes, and impurity transport codes. We discuss selected science and modeling/computational challenges in this area and our ideas for achieving these goals; this from the standpoint of our existing simulation codes. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)